DESIGNING LEMLEMTAK ACTIVITY IN TEACHING DESCRIBING PERSON FOR SPEAKING - Oktavia, Dessy; Rosnija, Eni; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research was conducted to investigate the studentsâ€™ need in learning describing person especially in speaking section, to design Lemlemtak activity in teaching describing person, and to evaluate whether or not the product is suitable for teaching describing person. The research involved the English teacher and the students at seventh grade of SMP-IT Al-Mumtaz Pontianak. The method of this research is development research which consists of three phases. They are analyze, design, develop, and evaluate or as known as ADDE. In this research, it was found Lemlemtak can help students enjoy the learning process of describing person in speaking section. The need analysis of the research obtained some information about the studentsâ€™ and teacher need in speaking section and the activity that usually used by the teacher. The model of Lemlemtak activity explained well in module which was designed by the writer. To conclude, Lemlemtak activity is considered good and suitable to use in teaching describing person for speaking at junior high school students especially students in seventh grade. The Lemlemtak activity is a fun and interesting activity which help students enjoy the learning process without any worries of making mistakes.Keywords: Lemlemtak, Describing Person, Speaking, Development ResearchÂ